2017
DOI: 10.1038/ncomms14806
|View full text |Cite
|
Sign up to set email alerts
|

EcR recruits dMi-2 and increases efficiency of dMi-2-mediated remodelling to constrain transcription of hormone-regulated genes

Abstract: Gene regulation by steroid hormones plays important roles in health and disease. In Drosophila, the hormone ecdysone governs transitions between key developmental stages. Ecdysone-regulated genes are bound by a heterodimer of ecdysone receptor (EcR) and Ultraspiracle. According to the bimodal switch model, steroid hormone receptors recruit corepressors in the absence of hormone and coactivators in its presence. Here we show that the nucleosome remodeller dMi-2 is recruited to ecdysone-regulated genes to limit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 50 publications
(73 reference statements)
5
35
0
Order By: Relevance
“…A gene ontology analysis identified a number of GO terms associated with a wide range of biological processes (Figure 6B). These included post-embryonic development and cell part morphogenesis in agreement with the established roll of dMi-2 in several differentiation processes (Kim et al, 2017;Kreher et al, 2017;Murawsky et al, 2001). GO terms related to the cell cycle or lipid metabolism were not strongly enriched.…”
Section: Ush-b and Dmi-2 Regulate Hemocyte-related Genessupporting
confidence: 66%
See 1 more Smart Citation
“…A gene ontology analysis identified a number of GO terms associated with a wide range of biological processes (Figure 6B). These included post-embryonic development and cell part morphogenesis in agreement with the established roll of dMi-2 in several differentiation processes (Kim et al, 2017;Kreher et al, 2017;Murawsky et al, 2001). GO terms related to the cell cycle or lipid metabolism were not strongly enriched.…”
Section: Ush-b and Dmi-2 Regulate Hemocyte-related Genessupporting
confidence: 66%
“…The function of dNuRD in hematopoiesis identified by our work solidifies the important role of this complex as a regulator of differentiation in Drosophila. We have previously shown that dMi-2 cooperates with transcription factors such as Tramtrack 69 or Kumgang to determine cell lineages in different developmental settings ranging from neurogenesis to spermatogenesis (Kim et al, 2017;Kreher et al, 2017;Murawsky et al, 2001;Reddy et al, 2010). In each of these scenarios a different lineage-specific transcriptional regulator (Tramtrack 69, Kumgang, Ush) utilises the ubiquitously expressed dMi-2 complex to establish lineage-and stage-appropriate gene expression programmes.…”
Section: Ush and Dnurd Cooperate In Hemocyte Differentiation In Vivomentioning
confidence: 99%
“…In agreement, no interaction between Su(H) and Mi-2 was detected ( Figure 5F) arguing that Mi-2 acts independently of the SuH-Hairless co-repressor complex to attenuate the expression of E(spl) genes. A second hypothesis was that Mi-2 reorganises the chromatin at target enhancers, preventing enhanced recruitment of Su(H) in the presence of Nact (Kreher et al, 2017). However, loss of Mi-2 had no effect on Su(H) recruitment in either Notch off or Notch on conditions ( Figure 5G) neither did it affect the levels of H3K27 trimethylation, the Altogether these data show that, although Mi-2 exerts a repressive effect on Notch target genes, even in Kc cells, it does so independently of Su(H) and Hairless.…”
Section: Mi-2 Loss Leads To De-repression Of E(spl)-c Genesmentioning
confidence: 99%
“…Fixation and immunohistochemistry of larval tissues were performed according to standard protocols. Primary antibodies were guinea pig anti-Dpn (1:2000) courtesy of Christos Delidakis; mouse anti-Mira [1:100, (Ohshiro et al, 2000)]; mouse anti-Pros MR1A (1:50, DHSB); rabbit anti-Ase (1:5000, courtesy of Y.N.Jan); rabbit anti-Mi-2 (1:10,000, courtesy of Alexander Brehm (Kreher et al, 2017). Mouse, rabbit or guinea pig secondary antibodies were conjugated to Alexa 488, 555, 568, 633 or 647 (Molecular Probes) or to FiTC, Cy3 or Cy5 (Jackson ImmunoResearch).…”
Section: Immunofluorescencementioning
confidence: 99%
See 1 more Smart Citation